Kesempatan Investasi, Kebijakan Dividen dengan Firm Size sebagai Variabel Moderasi - Satya Dewi, Dewa Ayu Mirah; Widanaputra, Anak Agung Gde Putu (E-Jurnal Akuntansi; Vol 31 No 12 (2021), 2021)
Dividend policy is one of the most important financial functions of a company. This is because the dividend policy has an influence on the company's stakeholders, both managers and investors. This study aims to determine the effect of investment opportunities on dividend policy with Firm Size as a moderating variable. This research was conducted on manufacturing companies on the Indonesia Stock Exchange for the 2015-2019 period. The population is 142 companies. Based on the purposive sampling method and the expenditure of outlier data, a sample of 34 companies was obtained. The data analysis technique used is Moderated Regression Analysis. The results of the analysis show that Firm Size does not weaken the effect of investment opportunities on dividend policy. The results of this study support the residual theory of dividend and agency theory. In addition, the results of this study can also be considered by companies in determining dividend policy and assisting investors in making investment decisions. Keywords : Investment Opportunity Set; Dividend Policy; Firm Size.